IMPLEMENTATION OF MOTOR DEVELOPMENT CHARACTERISTICS IN SEPAK TAKRAW TRAINING - Abdul Aziz Hakim; Achmad Sofyan Hanif (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This article will discuss about the characteristics of sports training that match the characteristic of child development. So hopefully by understanding it, sports training can achieve more optimal results. With the implementation of sports training in accordance with the characteristics of child development it will prevent achievement of peak performance too early. Through the theoretical adjustment between the main biomotor characteristics and the characteristics of motor development, in sepak takraw has been determined the initial age of training is 11 years old daughter and 12 year old son. So with the knowledge of this early age, can facilitate the making of training programs and sports football sepak takraw. So that the optimal achievement in sepak takraw can be achieved. Keywords: Characteristic of Motor Development, Biomotor Characteristics Sepak Takraw